HUBUNGAN TERPAAN WEB SERIES “SORE” DENGAN NIAT BELI TROPICANA SLIM STEVIA PADA MASYARAKAT DENPASAR - Eriyanti, Andiana Dwi; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT YouTube is the most favorite medium of view. The hgh traffic of YouTube visitors becomes the main attraction for companies to advertise in it. Web series is one of the forms of internet viewing on YouTube. Web series with soft selling technique seeks to create the impression and appeal emotionally so that a brand can be remembered through the terms of stories brought. The web series